Analisis Usahatani dan Saluran Pemasaran Biji Kakao di Kecamatan Juhar Kabupaten Karo Provinsi Sumatera Utara - Antri Sianturi, Meri Juli; Lubis, Zulkarnain; Siregar, Tumpal H.S. (Universitas Medan Area, 2020)
This study aims to (1) Know the cost elements of farming; (2) To know the financial feasibility of cocoa farming through analysis of B/C ratio and R/C ratio; (3) to know the cost structure of farming; (4) Analyzing the acceptance and income of cocoa farmers (5) Knowing the cocoa bean marketing system; (6) Knowing the cost, profit, margin and marketing efficiency of each marketing agencies, as well as the large farmer's share obtained by cocoa farmers in Kecamatan Juhar, Karo District. Determination of location of research conducted by the method of